Pengembangan media pembelajaran berbasis camtasia studio pada mata pelajaran ilmu pengetahuan sosial (IPS) - DK Refia Putri; Lilik Sri Hariani; Walipah Walipah (Jurnal Riset Pendidikan Ekonomi, 2022)
This study aims to produce learning media products that are suitable for use in social science subjects (IPS) for social mobility material for class VIII students at SMPN 2 Wagir. This research includes research and development (R&D) with the Dick & Carey development model. The development of learning media is carried out in several stages, namely: needs analysis, material identification, student characteristics analysis, instructional objective analysis, product design/product manufacture, design validation, and product revision. This media development was validated by media experts, material experts, linguists, and field trials involving 32 students were carried out. Types of data obtained in the form of qualitative data and quantitative data. Data collection procedures used were observation, interviews, and questionnaires. Data analysis includes qualitative data analysis and quantitative data analysis. The results showed that the development of learning media based on Camtasia Studio in social science subjects (IPS) class VIII SMPN 2 Wagir was feasible to use. This is indicated by; the results of the media expert validation were included in the "very feasible" category with a score of 93%, the material expert validation results were included in the "very feasible" category with a score of 90%, the linguist validation results were included in the "very feasible" category with the score obtained by 95%. The results obtained in the field trial assessment were 88% (very good).